Are biometric parameters of anterior segment of the eyeball influenced by type 2 diabetes? - Dmuchowska, Diana; Kraśnicki, Paweł; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Mechanisms related to the toxicity of hyperglycemia such as: enhanced activity of the polyol pathway, oxidative stress and formation of advanced glycation endproducts contribute to various ophthalmic complications in the course of diabetes. They lead to earlier cataract formation, increased lens weight and make shallow anterior chamber, with all subsequent consequences. Purpose: To answer the question whether biometric parameters of anterior segment of the eyeball are influenced by type 2 diabetes, at the stage when the lens is still transparent, so before cataract development. Material and methods: Fifty subjects (28 women and 22 men), at the age of 63.3 ± 11.3 years were enrolled in this prospective study. They were divided in 2 groups: patients with type 2 diabetes (24 subjects) and analogous age group in good general health – control group (26 subjects). None of the tested individuals presented lens opacities. The planned biometric measurements included: central corneal thickness, anterior chamber depth and axial lens thickness. The data were statistically analyzed. Results: There was no difference between the groups of both proven and potential parameters that are associated with biometric measurements of the anterior segment of the eyeball, such as: gender, age, smoking and axial length of the eye. In diabetic patients, as opposed to the subjects in the control group, statistically significantly increased lens thickness (4.78 ±0.50 mm vs 4.43 ± 0.50; p = 0,016), central corneal thickness (561.5 ± 31.6 μm vs 542.2 ± 35.2; p = 0.047), and the tendency for shallow anterior chamber (3.06 ± 0.40 mm vs 3.22 ± 0.38; p = 0.159), were observed. In patients with diabetes there was no association of the biometric parameters values with the duration of diabetes and presence of diabetic retinopathy. Conclusions: Type 2 diabetes contributes to increased axial corneal and lens thickness at the stage when the lens is transparent, albeit it does not significantly affect anterior chamber depth.